Saint Kitts and Nevis. Significant Achievements 2023 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
Saint Kitts and Nevis made significant strides in agricultural health and food safety (AHFS) in 2023, with support from the Inter-American Institute for Cooperation on Agriculture (IICA). Efforts included importing and cultivating 1000 banana plants resistant to Fusarium oxysporum f. sp cubense TR4, a fungal disease threatening CARICOM countries. Technical assistance was provided to combat African Swine Fever (ASF) and enhance plant pathology and integrated pest management (IPM) skills among agricultural officers and farmers. IICA facilitated international engagement through CODEX meetings and training sessions on ASF and ePhyto. Additionally, IICA's Single Fund initiative advanced agricultural development through study tours, consultations, and training sessions, particularly focusing on poultry production and management. The Premier of Nevis acknowledged IICA's contribution to the burgeoning broiler industry. Furthermore, IICA supported initiatives like the St. Kitts Beekeepers Cooperative and the St. Kitts Nevis Association of Persons with Disabilities (SKNAPD) in securing funds for apiculture and urban farming projects, respectively. Progress was made on the Saint Kitts and Nevis Climate Smart Agriculture Project (SKN CSA-P) under the Green Climate Fund (GCF) Simplified Approval Process (SAP), fostering collaboration between various stakeholders. These endeavors signify a concerted effort towards agricultural sustainability, resilience, and inclusivity in Saint Kitts and Nevis.